2008
DOI: 10.1111/j.1744-1617.2008.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Relocation, Research, and Forensic Evaluation: Part Ii: Research in Support of the Relocation Risk Assessment Model

Abstract: The forensic risk assessment model for child custody relocation cases was described by Austin (2000a, 2000b). It is a research‐based, actuarial predictive model designed to assist evaluators in organizing data for the complex relocation case. It is only the first step in the forensic relocation analysis. The model can serve as a heuristic for decision makers who are in a position of trying to resolve the decisional dilemmas associated with relocation. The research basis for the model is more fully described. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 94 publications
1
29
0
5
Order By: Relevance
“…FG is an essential risk management component in the implementation of a long distance plan. How gatekeeping analysis is applied to relocation cases has been discussed in the literature (Austin, 2008(Austin, , 2012. Judges usually are not going to approve a proposed relocation when there has been Unjustified RG, but the fact pattern and/or legal context may result in a child relocating with the parent even though there is an unfavorable pattern of gatekeeping.…”
Section: Applying Gatekeeping To Child-related Issues In Litigationmentioning
confidence: 99%
“…FG is an essential risk management component in the implementation of a long distance plan. How gatekeeping analysis is applied to relocation cases has been discussed in the literature (Austin, 2008(Austin, , 2012. Judges usually are not going to approve a proposed relocation when there has been Unjustified RG, but the fact pattern and/or legal context may result in a child relocating with the parent even though there is an unfavorable pattern of gatekeeping.…”
Section: Applying Gatekeeping To Child-related Issues In Litigationmentioning
confidence: 99%
“…Research that explores the impact of local moves on children in multiple contexts has been relied on within the court system in the absence of empirical evidence on the impact of relocation specific to the context of separation and divorce (Austin, 2008a(Austin, , 2008b(Austin, , 2012Braver et al, 2003;Kelly & Lamb, 2003;Wallerstein & Lewis, 1998), such as studies that have reported connections between a students' mobility and poorer academic and developmental outcomes (Wood et al, 1993). Caution is needed when interpreting these results and generalizing them to a separation and divorce context given that studies that examine mobility in general do not always account for mediators that could be affecting the negative outcomes associated in the literature with frequent mobility, such as employment issues or living in high-risk areas.…”
Section: Downloaded By [University Of Otago] At 07:28 21 July 2015mentioning
confidence: 99%
“…Moreover, it is important to compare the child's likely adjustment, well-being, and development associated with the two proposed residential living arrangements (Austin, 2000a(Austin, , 2008b. First, more than any other type of custody dispute, evaluators need to be well versed in the legal statutes and case law, child custody procedures, and relevant divorce/relocation literature.…”
Section: Complexity Of Relocation Casesmentioning
confidence: 99%
“…The literature supports this possibility, suggesting a heightened risk for relationship harm when the distance between the households is greater and the children are younger (Austin, 2008b(Austin, , 2010Hetherington & Kelly, 2002;McHenry, Price, Fine, & Serovich, 1992). The moving parents wants to relocate with the children in order to improve their quality of life and/or to pursue new opportunities, such as better job, new relationship, family support, and so on.…”
Section: Complexity Of Relocation Casesmentioning
confidence: 99%
See 1 more Smart Citation